Análisis del valor y su influencia en el rediseño y la sustitución de componentes en las mypes del sector textil de confecciones en la región Arequipa - De la Gala Velásquez, Bernardo Ramón Dante (2019)
The value analysis, redesign and replacement of components are key activities in the performance of microenterprises in the Arequipa textile sector; however, in practice,they are not carried out in a systemic way, taking place with delays in execution time and deficiencies in the communication channels, motivation and creativity, amongothers, which means that they are not used properly (Chen Su, 2017; Aminoroaya Yamini, 2016). A preliminary step to redesign and/or replace components is the analysis of value, according to the proposal of Meeker and McWilliams (2011); that way, if textile entrepreneurs apply it according to what the value analysis approach raises, the business competitiveness of the sector could be improved. The purpose of this research is to demonstrate the influence that value analysis has on the use of redesign and component replacement techniques, widely utilized to the productive work of this type of companies. Regarding the methodology that was applied, it should be mentioned that a sampling was carried out for convenience using Likert scale measurement questionnaire to 157 microentrepreneurs in the Arequipa region, and that a reliability level of 0.83 was obtained. The study determined a high level of use of these techniques above 63% in the analysis of the value, while the redesign and replacement of components registered an average use of 52.90%. Additionally, an influence of the value analysis on the redesign and replacement of components was identified, in both cases with high results found through the system of structural equations (SEM); and it was also determined that there is no mediation of the redesign or replacement of components in turn.